4CPS-059 Effectiveness of meropenem treatment in critical patients: pharmacokinetic study. (March 2019) - Idoate, AI; Aldaz, A
Abstract : Background: Pharmacokinetic/pharmacodynamic efficacy index (PK/PD) for carbapenems, in critical patients, is the maintenance of a free concentration drug, 4–5 times above the minimum inhibitory concentration (MIC) in the isolated germ during 100% of the dosage range. Ensuring this goal is important and requires the use of pharmacokinetic monitoring (TDM). Purpose: Analyse the efficacy of pharmacokinetic optimised meropenem's regimen based on PK/PD criteria and compare it with empirical carbapenem's regimen adjusted by renal function in patients admitted to the intensive care unit. Material and methods: Naturalistic retrospective, observational cohort study, carried out in critically ill patients treated with meropenem from May 2011 to December 2017. Patients were divided into two cohorts: cohort A if they had pharmacokinetic intervention or cohort B if not. In pharmacokinetic analysis two serum samples per patient were extracted (peak and elimination point) to quantify total and free concentration of meropenem. Individual pharmacokinetic parameters were estimated by the Sawchuk–Zaske method to find out what percentage of time, free concentration exceeded four times MIC of isolated germ and dosage regimen was adjusted when necessary. When CMI was not available, the epidemiological limit of EUCAST(ECOFF) 2 mcg/mL was used. Clinical and bacteriological responses were the main goals. Data was analysed using STATA12.0. Propensity score (PS) of each patient was calculated and patients in cohort A were compared and paired one by one with those of cohort B with similar PS. Results: One-hundred and fifty-six patients were included, 78 in each cohort after matching by PS. Main antimicrobial treatments were targeted (71.8% in cohort A and 73% in cohort B). Median duration of meropenem was 11 days (range: 2–31 days). In cohort A, dose adjustment was performed in 65% (n=51) of patients and in up to 88% (n=45) of them it was recommended to reduce dose or extend dosage range. Cohort A was associated with clinical improvement (OR: 1.624, 95% CI: 0.82 to 3.23, p=0.167), bacteriological (OR: 0.636, 95% CI: 0.27 to 1.48, p=0.292), fever resolution (OR: 2.415; 95% CI: 1.04 to 5.61, p=0.040), decreased inflammatory parameters (statistically significant PCR (p=0.0065) and procalcitonin (p=0.0099), lower hospital mortality (OR: 1.184; 95% CI: 0.52–2.68, p=0.685) and early mortality during first 14 days after hospital discharge (OR: 0.7505, 95% CI: 0.1184 to 4.76, p=0.761), against cohort B. Conclusion: Meropenem daily dose was decreased in 56% of critical patients monitored. TDM is important in fighting against antimicrobial resistance, it is a guarantee of safety and it allows a reduction in healthcare cost. References and/or acknowledgements: https://www.ijaaonline.com/article/S0924–8579(16)30268–0/fulltext No conflict of interest.